MEKANISME PERUMUSAN PRODUK HUKUM DAERAH (Studi Penyusunan Peraturan dan Keputusan Gubernur Provinsi Jawa Tengah) - Ima Lutfiana; Aufarul Marom (Journal of Public Policy and Management Review, 2018)
To execute the public services, it requires the legal norms in the form of local law products intentionally made by the government as the basis of public policy implementation that can provide the explicit arrangements and ensure the provision of public services in accordance with the general principles of the good government. The Legal Bureau of Regional Secretariat of Central Java has a duty to prepare the local law products in Central Java Province with the Regional Apparatus Organization (OPD) in charge. Based on the Legal Bureau data, in 2013-2017 the local law products in the form of the Regulations and Decisions of Governor are not appropriate between the proposed products and produced products. The aims of this study are to analyze the formulation mechanism of local law products in the Regulations and Decisions of Central Java Province’s Governor and to understand the factors affecting the preparation. The method used in this study is the qualitative descriptive. The result of this study shows that the process of Regulations and Decisions preparation of Central Java Province’s Governor is in accordance with the mechanism of public policy formulation. The factors affecting the process of Regulations and Decisions preparation of Central Java Province’s Governor are the external pressure, the old habit, the personality traits, and the external groups. Some suggestions that can be given are the Legal Bureau should propose the employee addition, the Regional Apparatus should propose the provision of training and the certification for the regulation drafters, and the Legal Bureau and the Regional Apparatus need to improve their coordination and communication.